Ugandan Adolescents' Attitudes Toward, and Shared Activities with, Same- and Other-Gender Peers and Friends. Issue 5 (July 2022) - Faragó, Flóra; Xu, Jingyi; Eggum-Wilkens, Natalie D.; Zhang, Linlin; An, Danming; Kim, Eunjung; Adams, Emily
Ugandan adolescents ( n  = 202, 54% girls; M age  = 14.26) answered closed- and open-ended questions about the gender composition of friends and attitudes about, and activities with, same- and other-gender peers and friends. Adolescents' friendships were somewhat gender segregated, although other-gender friendships were present. Positive attitudes about same- and other-gender peers and friends were prevalent. Girls and boys displayed similar attitudes about same- and other-gender peers, with the exception of boys reporting more positive attitudes toward boys. Adolescents enjoyed the following aspects of same- and other-gender friendships: talking about problems, receiving help, sharing items and activities, receiving advice about romance and puberty, and receiving help with schoolwork. Adolescents engaged with mixed-gender peers for most shared activities, although gender segregation was present for certain activities (e.g., playing sports). Results may inform programs that support positive peer interactions among youth in sub-Saharan Africa.